PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII-8 SMP NEGERI 20 PEKANBARU - Oktaviani, Nona; Saragih, Sehatta; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a classroom action research that aims to improve the learning process and improve the learning outcomes of mathematics by applying the Problem Based Learning (PBL) model. The subjects of this study were students of class VIII-8 of SMP Negeri 20 Pekanbaru in 2018/2019 academic year, totaling 42 people with heterogeneous levels of academic ability. This study consists of two cycles and each cycle consists of the stages of planning, implementation, observation and reflection. Every end of the cycle is held Daily Deuteronomy (UH). Data collection is done through UH observations and tests. Data analysis was carried out by descriptive narrative analysis and descriptive statistical analysis. Actions are said to be successful if there is an improvement in the learning process and the number of students who achieve the Minimum Completion Criteria (KKM) increases in UH I and UH II. The results of the study showed an increase in the activities of teachers and students. Most students are seen as actively participating in the learning process, such as discussing, presenting Student Worksheets (LKPD), responding to their friends' presentations and giving learning conclusions. Students also try to solve the problems that the teacher gives them well. Therefore it can be said that there is an improvement in the learning process in the cycle. In addition, the number of students who reached KKM on the basic score, UH I (cycle I), UH II (cycle II) were 15 people (35.71%), 23 people (54.76%), and 33 people (78.57%) respectively. . The percentage of KKM achievement shows an increase from before the action to after the action so that it can be said that the learning outcomes of students also increase. The results of this study indicate that the PBL model can improve the learning process and improve the mathematics learning outcomes of students of class VIII-8 in SMP Negeri 20 Pekanbaru in the odd semester of the 2018/2019 academic year on material relations and functions.Key Words: Mathematic learning evaluation, Classical research, Problem based learning.